(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
The annotaded list of rare and threatened species of the flora of Kryvyi Rih that includes 157 species of vascular plants with international, national and regional phytosozological status is presented. Of this number, actually 14 species belong to category 0 (disappeared species), 40 species – to category 1 (vanishing), 33 species – to category 2 (vulnerable), 59 species – to category 3 (rare), 11 species – to category 4 (indefinite species). Most plants that are guarded contain families of Asteraceae (16 species), Fabaceae (12), Rosaceae and Poaceae (for 11 species). Except guard of species in the network of objects of the naturallyprotected fund for the industrial regions additional ways of conservation of rare and vanishing species of natural flora are needed: cultivation in botanical gardens, deployment in planting of greenery of city and for recultivation of broken lands.